The correlation between the phenolic composition and biological activities of two varieties of Brazilian propolis (G6 and G12) - Ingridy Simone Ribeiro Cabral; Tatiane Luiza Cadorin Oldoni; Severino Matias de Alencar; Pedro Luiz Rosalen; Masaharu Ikegaki (Universidade de São Paulo, 2012)
Biological assays that have been performed on different types of Brazilian propolis have shown that type 6 propolis (G6) has a strong antimicrobial activity and a low flavonoid content. This study aimed to evaluate the correlation between the phenolic composition and the biological activities displayed by propolis G6 from the state of Bahia and green propolis, also known as type 12 (G12). The values of the flavonoids and the total phenolics in propolis G6 were different than those in propolis G12. Although the G12 variety presented greater antioxidant activity, propolis G6 proved to have greater antimicrobial and cytotoxic activities. The results showed that the phenolic compounds may not be the only compounds responsible for the biological activity. More detailed studies of the chemical composition and an assessment of the biological activity are required to establish the quality of propolis. Ensaios biológicos realizados com diferentes tipos de própolis brasileira têm mostrado que a própolis do tipo 6 (G6) tem forte atividade antimicrobiana e menor teor de flavonóides. Este trabalho teve como objetivo avaliar a correlação entre a composição fenólica e atividades biológicas apresentadas pela própolis G6, do Estado da Bahia, e a própolis verde, do tipo 12 (G12). Os teores de flavonóides e fenólicos totais na própolis G6 foram diferentes dos teores da própolis G12. Apesar da G12 apresentar maior atividade antioxidante, a própolis G6 apresenta maior atividade antimicrobiana e citotóxica. Os resultados mostraram que os compostos fenólicos não são os únicos compostos responsáveis pela atividade biológica da própolis. Estudos mais específicos da composição química, em adição à avaliação das atividades biológicas, são requeridos para determinar a qualidade da própolis.